Review: Jesus, Trauma & Psychoanalytic Technique - Miller, Adam S. (The journal for cultural and religious theory, 2008)
Bruce Fink. Fundamentals of Psychoanalytic Technique: A Lacanian Approach for Practitioners. W.W. Norton, New York, 2007. 301 pp. ISBN-10:0393705080; Marcus Pound. Theology, Psychoanalysis, Trauma. SCM Press, London, 2007. 188 pp. ISBN-10: 0334041392